2010
DOI: 10.1002/anie.201003212
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Photocycloaddition of 3‐Hydroxyflavones: Synthesis and Evaluation of Rocaglate Derivatives as Inhibitors of Eukaryotic Translation

Abstract: Shedding light on translation: A light‐driven, biomimetic [3+2] cycloaddition has been achieved with the synthesis of a series of rocaglate derivatives. Mechanistic data suggest the possibility for donor–acceptor interactions and the involvement of triplet biradicaloids in the photoexcited state. Several new rocaglate derivatives approach the potency of the anticancer agent silvestrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 61 publications
0
56
0
Order By: Relevance
“…This difference in protein synthesis inhibition across different mRNAs is one possible explanation for the observed therapeutic index of cyclopenta[ b ]benzofurans [e.g., silvestrol ( 2 ) and the rocaglamide derivative, rohinitib ( 51 , Figure 6)] in mouse models. 56,63,72,79,85 Pelletier’s group first demonstrated that the translation initiation factor eIF4A was the likely target of the cyclopenta[ b ]benzofurans, using biochemical assays to show that 1- O -formylaglafoline ( 52 , Figure 6) and silvestrol ( 2 ) stimulated an abnormal interaction of eIF4A with mRNA and prevented successful assembly of the mRNA:eIF4A dimer with the eIF4F translation initiation complex. 66,72 As noted previously, this finding was separately confirmed by two groups using genetic and biochemical approaches.…”
Section: Recent Biological Evaluation and Mechanism-of-action Studimentioning
confidence: 99%
“…This difference in protein synthesis inhibition across different mRNAs is one possible explanation for the observed therapeutic index of cyclopenta[ b ]benzofurans [e.g., silvestrol ( 2 ) and the rocaglamide derivative, rohinitib ( 51 , Figure 6)] in mouse models. 56,63,72,79,85 Pelletier’s group first demonstrated that the translation initiation factor eIF4A was the likely target of the cyclopenta[ b ]benzofurans, using biochemical assays to show that 1- O -formylaglafoline ( 52 , Figure 6) and silvestrol ( 2 ) stimulated an abnormal interaction of eIF4A with mRNA and prevented successful assembly of the mRNA:eIF4A dimer with the eIF4F translation initiation complex. 66,72 As noted previously, this finding was separately confirmed by two groups using genetic and biochemical approaches.…”
Section: Recent Biological Evaluation and Mechanism-of-action Studimentioning
confidence: 99%
“…Notably, the above (3+2) photocycloaddition involving oxidopyrylium ions allowed facile access to several other rocaglate natural products including rocaglaol, rocaglamide, silvestrol, episilvestrol, as well as several derivatives (e.g., 30 – 32 ) (Figure 1). 18 …”
Section: Heteroatom-substituted Oxyallyl Cationsmentioning
confidence: 99%
“…This spectacularly concise and novel method of accessing all three flavagline core types through a biomimetic pathway was used in an enantioselective synthesis of rocaglamide, 14 rocaglaol, 14 silvestrol, 15 and a variety of other natural and unnatural rocagamide derivatives. 16 In 2009, our group published an annotated study on the total synthesis of rocaglamide which harnessed an oxidation-initiated Nazarov cyclization. 17 In addition to the complete syntheses outlined above, a number of other approaches have been used to construct rocaglamide derivatives, including those published by Feldman, 18 Umezawa, 19 Schoop, 20 Ragot, 21 Magnus, 22 and Moser.…”
Section: Introductionmentioning
confidence: 99%